Information and public choice: - Islam, Roumeen (The World Bank, 2008)
The ability of the media to affect outcomes in economic and political markets has been well documented. News reporting and advertising influence consumer behavior in goods and services markets by revealing (or selectively revealing) information about a product, acting as agenda setters to influence consumer demand, or enhancing competition in markets by alerting consumers to substitutes. In political markets, they can affect behavior by informing voters about a politician's views or actions, enlightening citizens to outcomes of public policy, or taking a stance on political, social, or economic issues. For businesses, households, and most others, the media is the main source of information on public policy choices and current social and economic conditions. As a result, what news the media chooses to gather, analyze, and disseminate and the slant they choose to put on what they report is of consequence. Information and Public Choice addresses the factors that affect the content and reach of news coverage as well as its impact on public policy.